PENGARUH RETURN ON INVESTMENT (ROI) DAN EARNINGS PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN DENGAN PERCEIVED RISK SAHAM SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2013-2016). - Rudi Nursetyo; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
AbstractThis study aims to 1) Know the effect of Return on Investment (ROI) on StockPrice Manufacturing Companies listed in Indonesian Stock Exchange year 2013-2016,2) Knowing the influence of Earning per Share (EPS) on Stock Price ManufacturingCompanies listed in the Indonesian Stock Exchange year 2013-2016, 3) Knowing theinfluence of Perceived Risk Shares on ROI relation to Stock Price of ManufacturingCompany listed on Indonesian Stock Exchange year 2013-2016, 4) To know the effectof Perceived Risk Shares on EPS relation to Stock Price of Manufacturing Companyregistered in Indonesian Stock Exchange year 2013-2016, 5) Knowing the influence ofPerceived Risk of Share on ROI and EPS relation to Stock Price of ManufacturingCompany listed in Indonesia Stock Exchange year 2013-2016, 6) Knowing influence ofReturn On Investment and Earnings Per Share to Share Price Manufacturing Companieslisted on the Indonesian Stock Exchange 2013-2016.The population in this research is 132 manufacturing companies listed inIndonesian Stock Exchange year 2013-2016. After selecting according to the method ofpurposive sampling in the population, there were 12 manufacturing companies used assamples. Data collection method used is documentation method. Data analysistechniques use simple linear regression analysis, and Moderated Regression Analysis(MRA). Based on the results of the study, Return on Investment (ROI) has a positiveand significant effect on Stock Price Manufacturing Companies listed in IndonesianStock Exchange 2013-2016. Earnings per Share (EPS) has a positive and significanteffect on Stock Price of Manufacturing Companies listed in Indonesian Stock Exchange2013-2016. Perceived Risk Shares do not negatively and significantly affect the StockPrice of Manufacturing Companies listed in Indonesian Stock Exchange 2013-2016.Perceived Risk Shares have a significant negative effect on EPS relation to Stock Priceof Manufacturing Company listed on Indonesian Stock Exchange 2013-2016. PerceivedRisk Shares do not negatively affect and significant on the relationship of ROI and EPSto Stock Price Manufacturing Companies listed in the Indonesian Stock Exchange 2013-2016 years. ROI and EPS have a positive and significant effect on Stock Price ofManufacturing Company listed on Indonesian Stock Exchange year 2013-2016.Keywords: Return On Investment (ROI), Earnings Per Share (EPS), Perceived Risk ofShares, Stock Price of the Company.